The Effect of F:S Ratio, Temperature, Particle Diameter, and Mixing Speed in The Dispersive Contact Batch Extraction of Phaleria macrocarpa Fruit Using 70%-v Ethanol Solvent - Susiana Prasetyo S (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Phaleria macrocarpa is a native Indonesian plant from Papua, which has a high content of antioxidant and antimicrobial bioactive compounds. Therefore, it offers a very high potential to be utilized as the raw material for food preservative and supplement, as well as herbal medicine. This study was conducted for the development of the extraction and separation technology to obtain the useful bioactive compounds within a high quality extract from Phaleria macrocarpa fruit. Solid-liquid extraction was performed by dispersive contact using 70%-v ethanol in a 2 L batch extractor. The extraction process involved some variations of the process variables, namely F:S ratio (0.025 – 0.05 g/mL), temperature (28 - 52°C), particle effective diameter (0.22 – 0.90 cm), and mixing speed (140 – 400 rpm). The experimental series were carried out by using a Box-Behnken design with 3 center points, in order to comprehend both responses of yield oleoresin time profile and antioxidant activity (as DPPH equivalent). The experiments by varying those process variables could be used to estimate the volumetric mass transfer coefficient (kLa) using macroscopic balance based on a lumped model. The extraction optimum conditions were found at F:S ratio of 0.03 g/mL; temperature at 28°C; mixing speed 400 rpm; and particle diameter of 0.76 cm under which the highest yield of 94.56% , DPPH equivalent of 3.7364 μmol DPPH/mg crude extract, and mass transfer coefficient of 0.0192 s-1 were obtained.